2007
DOI: 10.1002/cmdc.200700103
|View full text |Cite
|
Sign up to set email alerts
|

Designed Amyloid β Peptide Fibril—A Tool for High‐Throughput Screening of Fibril Inhibitors

Abstract: Amyloid beta peptide (Abeta) fibril formation is widely believed to be the causative event of Alzheimer's disease pathogenesis. Therapeutic approaches are therefore in development that target various sites in the production and aggregation of Abeta. Herein we present a high-throughput screening tool to generate novel hit compounds that block Abeta fibril formation. This tool is an application for our fibril model (Abeta(16-37)Y(20)K(22)K(24))(4), which is a covalent assembly of four Abeta fragments. With this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…The structures of the compounds are shown in Table 1 and were selected based on similarity to existing anti-Aβ compounds, as well as grouped into single and double ring structures. For example the following structures were similar to existing anti-amyloids: nialamide ≈ nordihydroguaiaretic [54], isonicotinic acid hydrazide and 4-amino benzhydrazide ≈ o-vanillin [55], 1,1′-diphenylhydrazine hydrochloride ≈ 4,4′-dihydroxybenzophenone [54], hydralazine ≈ napthoquinone and juglone [55], and finally indole-3- acetic hydrazide ≈ similar substructure to azure C [55] and myrecetin [54]. Additionally, while hydrazides are reactive compounds, they have been and can be used as drugs.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the compounds are shown in Table 1 and were selected based on similarity to existing anti-Aβ compounds, as well as grouped into single and double ring structures. For example the following structures were similar to existing anti-amyloids: nialamide ≈ nordihydroguaiaretic [54], isonicotinic acid hydrazide and 4-amino benzhydrazide ≈ o-vanillin [55], 1,1′-diphenylhydrazine hydrochloride ≈ 4,4′-dihydroxybenzophenone [54], hydralazine ≈ napthoquinone and juglone [55], and finally indole-3- acetic hydrazide ≈ similar substructure to azure C [55] and myrecetin [54]. Additionally, while hydrazides are reactive compounds, they have been and can be used as drugs.…”
Section: Resultsmentioning
confidence: 99%
“…As noted, these findings confirm that Aβ42 fusions expressed in plant cells can be used to detect small molecule and phytochemical inhibitors effective in preventing the misfolding/aggregation of Aβ42 peptides, and provide support for the use of this system for drug screening. A number of screening methods have been developed to detect Aβ aggregation inhibitors [47][48][49][50]. Most use turbidity or thioflavin T-binding assays to assess molecules that interfere with the formation of fibrillar aggregates from pure synthetic Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, AFM images of the Ab 1-40 assays showed no inhibition of fibril formation compared to the control (Figure 4 A and B). Considering that filter-effects can be ruled out for 6 and 7 because they do not absorb at the wavelengths of fluorescence excitation or emission, [26] fluorescence inhibition is probably caused by direct competition against the fluorescent reporter ThT for binding to the fibrils, a typical feature of polyphenolic compounds. [26] The same effects were observed with the phenolic bis-oximes 10, 11, 14 with IC 50 values in the 10-30 mm range, but no effective inhibition of fibril formation when tested by AFM.…”
mentioning
confidence: 99%
“…In summary, screening for inhibition of amyloid fibril formation using our recently reported microtiterplate fluorescence assay [26] was implemented for the first time to discover new inhibitors in a library of oxime oligomers. Investigation of initial hits by AFM revealed that the smaller oxime and dioxime hits inhibited fluorescence without blocking amyloid formation, presumably by direct competition with the fluorescence label ThT for binding to the fibrils.…”
mentioning
confidence: 99%
See 1 more Smart Citation